Perilaku Konsumtif Followers Akun @discountfess Pada Media Sosial X - Rahma Mudhiyanti; Dian Alfia Purwandari; Sujarwo Sujarwo (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
Globalization brings many influences and changes in human life. The rapid dissemination of information obtained through social media can cause change. X account @discountfess as a forum that favolitates the dissemination of information quickly and widely can influence a person's behavior, one of wich is consumprive behavior. This study aims to describe the consumptive behavior of folllwers account @discountfess at social media X, using a descriptive method of quantitative approach. Sampling was accidental sampling with 96 followers @discountfess account. Data collection techniques include observation, questionnaire, documentation and literature study. The results show that the consumptive behavior of followers account @discountfess that causes impulsive purchases in the moderate category of 57%, irrational purchase in the moderate category with a percentage 60% and waste in the high category with a percentage 52%.